Detection of wild house mice and other small mammals up trees and on the ground in New Zealand native forest. Issue 3 (3rd July 2018) - Innes, John; Kelly, Catherine; Fitzgerald, Neil; Warnock, Morgan; Waas, Joseph
ABSTRACT: Determining pest mammal impacts and abundance in forests requires an understanding of how target species use vegetation compared with the ground. We used a novel device combining footprint tracking with bite detection to survey for mammals at four levels in New Zealand forests that had house mice ( Mus musculus ) alone, and all widespread New Zealand mammals, including house mice, ship rats ( Rattus rattus ) and brushtail possums ( Trichosurus vulpecula ). When alone, house mice were detected at 93%, 35%, 17% and 0% of devices on the ground, in shrubs, in the subcanopy and canopy, respectively, but in a pilot study at one site were detected 11 m above ground. When all small pest mammals were present, house mice were scarce and none were detected up trees. Ship rats and possums were detected mostly on the ground, but also at all surveyed heights. The study confirms that mice, ship rats and possums are all potential above-ground predators, but suggests that targeting them for control and monitoring can reasonably be undertaken on the ground.